ANALYSIS OF BIRTH QUARTILE OF PROFESSIONAL SOCCER PLAYERS - Moraes, Luiz Carlos Couto de Albuquerque (2009)
The categorization of the time of birth (quartiles) is shown to be a factor which influences the development of a talent in soccer, which in its structure has the division of categories into age groups. The aim of the present study is to assess and identify the quartiles of birth in professional players at different levels: the Brazilian National Championship First Division (20 clubs), the Second Division (16 clubs) and Libertadores da America Cup (32 clubs). Data of 2,073 players were collected and analyzed using the chi-square test. Differences were found in the quartile as well as the birth semester in all the three competitive levels analyzed. It was therefore concluded that the quartile of birth is a factor that has an influence in player selection, both in Brazil and in South America.